Mapping deforestation and forest degradation using CLASlite approach in Eastern Churia of Nepal - Khanal, S.; Khadka, A. (Banko Janakari, 2016)
Monitoring deforestation and forest degradation is essential for forest conservation and sustainable management. Those activities have become more relevant in order to get reference emission level required for Reducing emissions from deforestation and forest degradation (REDD) initiative. The study aimed to assess forest degradation and deforestation in the Churia region of Eastern Nepal using CLASlite approach. This approach is based on Spectral Mixture Analysis and provides highly automated technique for forest cover, deforestation and forest degradation mapping. The Landsat imageries of 2002 and 2013 were processed for estimation of deforestation and forest degradation. The validation of results based on the high-resolution multi-temporal Google Earth imageries and the field sample plots indicated that CLASlite approach could be feasible approach to monitor forests for deforestation and degradation. The results can be further improved by including more frequent time-series observation from Landsat. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 17-23, 2016